PELAKSANAAN KEBEBASAN BERAGAMA DI INDONESIA (EXTERNAL FREEDOM) DIHUBUNGKAN IJIN PEMBANGUNAN RUMAH IBADAH - Putri, Nella Sumika (Jurnal Dinamika Hukum, 2011)
Recently, Indonesia faced issues about freedom of religion, in particular for construction the house of worship. It is part of freedom of worship which is element from freedom of religion and it should protected by State. eventhough State in implementation those right can make some limitation. Joint Decree 2006 is a form of restriction provided by the State to maintain public order. The implementation of freedom of religion is highly depend on the tolerance among religious community, particularly in the scope of forum externum. Cooperation beetwen all parties, i.e State as policy makers and implementers, religious leaders as a role model for the followers and society plays an important role in maintaining inter-religious harmony. Keywords: human rights, freedom of religion, construction the house of worship